2016
DOI: 10.1155/2016/7230626
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Risk Factors for Gastroduodenal Ulcer in Romanian Low-Dose Aspirin Consumers

Abstract: Background. Aspirin use for cardiovascular or cancer prevention is limited due to its gastrointestinal side effects. Objective. Our prospective, observational case-control study aims to identify the predictive factors for ulcers in low-dose aspirin consumers (75–325 mg/day). Methods. The study included patients who underwent an upper digestive endoscopy and took low-dose aspirin treatment. Results. We recruited 51 patients with ulcer (ulcer group) and 108 patients with no mucosal lesions (control group). In un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 37 publications
2
14
1
Order By: Relevance
“…The consumption of gastro-toxic drugs (NSAIDs, LDA), was less frequent in patients with CHF, while anticoagulants were more frequent, as the international thera-peutic guideline recommends their use in treatment or secondary prevention of the underlying conditions. Among all questioned variable, the aggressive effect of antiplatelet therapy (LDA), in a vulnerable congestive gastric mucosa was supported by our present and past results, while the role of anticoagulants should be further investigated in larger studies [22]. It has been demonstrated that daily LDA consumption reduces the risk of cardiovascular diseases, however, it also associates adverse effects, mostly in the gastrointestinal tract.…”
Section: Discussionsupporting
confidence: 73%
“…The consumption of gastro-toxic drugs (NSAIDs, LDA), was less frequent in patients with CHF, while anticoagulants were more frequent, as the international thera-peutic guideline recommends their use in treatment or secondary prevention of the underlying conditions. Among all questioned variable, the aggressive effect of antiplatelet therapy (LDA), in a vulnerable congestive gastric mucosa was supported by our present and past results, while the role of anticoagulants should be further investigated in larger studies [22]. It has been demonstrated that daily LDA consumption reduces the risk of cardiovascular diseases, however, it also associates adverse effects, mostly in the gastrointestinal tract.…”
Section: Discussionsupporting
confidence: 73%
“…Selection bias, for individuals with active PUD, could further not be ruled out of three studies. 17,23,30 Despite these limitations, the results of a sensitivity analysis limited to only higher quality studies did not differ greatly from the complete analysis. Some potential confounding factors could not be reconciled in this analysis.…”
Section: Discussionmentioning
confidence: 92%
“…Two final studies enrolled individuals on long-term LDA (≥1 month), who were undergoing endoscopy for investigation of primarily gastrointestinal symptoms. 23,30 Mean LDA dose ranged from 100-160 mg daily in five cross-sectional studies 3,24,28,29,31 and was not reported in the remainder.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations